2016
DOI: 10.3324/haematol.2015.135137
|View full text |Cite
|
Sign up to set email alerts
|

Risk assessment of relapse by lineage-specific monitoring of chimerism in children undergoing allogeneic stem cell transplantation for acute lymphoblastic leukemia

Abstract: A llogeneic hematopoietic stem cell transplantation is required as rescue therapy in about 20% of pediatric patients with acute lymphoblastic leukemia. However, the relapse rates are considerable, and relapse confers a poor outcome. Early assessment of the risk of relapse is therefore of paramount importance for the development of appropriate measures. We used the EuroChimerism approach to investigate the potential impact of lineage-specific chimerism testing for relapserisk analysis in 162 pediatric patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 28 publications
1
28
0
Order By: Relevance
“…This number increased slightly for STR-PCR in leukocyte subpopulations but was still lower than previously reported frequencies. 26,28 Likely, this low number is due to omission of samples closer than 30 days to diagnosis of relapse, as a detection of 5% recipient or more DNA in peripheral blood by STR-PCR is often detected in conjunction to diagnosis of morphological relapse in bone marrow, and This study has limitations, and results should be interpreted with caution. As it is a retrospective study, the frequency of samples was not controlled prospectively and is likely biased.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…This number increased slightly for STR-PCR in leukocyte subpopulations but was still lower than previously reported frequencies. 26,28 Likely, this low number is due to omission of samples closer than 30 days to diagnosis of relapse, as a detection of 5% recipient or more DNA in peripheral blood by STR-PCR is often detected in conjunction to diagnosis of morphological relapse in bone marrow, and This study has limitations, and results should be interpreted with caution. As it is a retrospective study, the frequency of samples was not controlled prospectively and is likely biased.…”
Section: Discussionmentioning
confidence: 89%
“…Two children had an episode of IMC using STR‐PCR in whole blood. This number increased slightly for STR‐PCR in leukocyte subpopulations but was still lower than previously reported frequencies . Likely, this low number is due to omission of samples closer than 30 days to diagnosis of relapse, as a detection of 5% recipient or more DNA in peripheral blood by STR‐PCR is often detected in conjunction to diagnosis of morphological relapse in bone marrow, and these samples are thus not included in this analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…And they confirm that the reappearance of recipient cells preceded hematological relapse in patients with acute leukemia may strengthen the hypothesis that these re-emerging host cells weaken the GVL effect of donor effector cell, possibly as the result of the induction of tolerance towards host antigens. Preuner et al (35) and Bader et al, (33) Patients with ALL who were not completely chimeric on day 28 after transplantation had increased risk of relapse, they concluded that within a median observation time of 4.5 years of ALL patients, the appearance of recipientcells after a period of pure donor chimerism in the CD34+ and CD8+ leukocyte subsets revealed adynamic indicative of significantly elevated riskof relapse or imminent disease recurrence. Depending on previous studies, which revealed that Lineage restricted chimerism is a very useful tool as to follow up post-transplant results (16) .…”
Section: Discussionmentioning
confidence: 99%